Penerapan Profil Pelajar Pancasila Melalui Kegiatan Pembiasaan Menyanyikan Lagu Wajib Nasional Dan Lagu Daerah di SDN 1 Lemahabang - Salsabila Quratu Aini; Nia Fatmawati; Pramurinda Aulia; Kayla Haifa Winarto; Hanikah Hanikah; Khujah Iis Farsyafat (Journal on Education, 2025)
The implementation of the Pancasila Student Profile is an important effort in shaping the character of Indonesia's young generation, especially in the Global Diversity dimension. This study aims to analyze the impact of the habituation of singing national and regional compulsory songs at SDN 1 Lemahabang on the application of national values and student solidarity. Using a qualitative approach and case study method, data was collected through observation and interviews with the principal, teachers, students, and parents. The results showed that this activity was able to increase students' love for the country, tolerance, and understanding of Pancasila values. However, obstacles such as students' lack of understanding of the meaning of songs require innovative approaches, such as technology integration and parental involvement. In conclusion, this habit is effective in strengthening students' national identity and solidarity, although it requires additional support for optimal results